Agrarian Reform: The Legal Protection of Ulayat Land for Indigenous Peoples - A. A. Istri Eka Krisna Yanti; Anak Agung Istri Ari Atu Dewi; I Gede Pasek Pramana; Anak Agung Angga Primantari (Warmadewa Press, 2026)
This study examines the recognition and management authority of the ulayat land of indigenous peoples after agrarian reform. The 1945 Constitution of the Republic of Indonesia and the Basic Agrarian Law recognize the rights of indigenous peoples and their ulayat rights. However, due to dilemmas regarding the protection and management of ulayat land, it is necessary to assess the extent of legal certainty in the governance of ulayat land for indigenous people. This research employs a normative legal methodology, incorporating both statutory and conceptual approaches. The findings reveal that land in Indonesia is ultimately controlled by the State, as provided for in Article 33 of the 1945 Constitution. State control is not absolute ownership and may be delegated to indigenous people. Agrarian reform, as formalized through Presidential Regulation No. 62 of 2023 and Ministerial Regulation ATR/BPN No. 14 of 2024, officially recognizes indigenous peoples. This occurs by issuing Land Parcel Identification Numbers (Nomor Identifikasi Bidang Tanah) and registering ulayat land in the Ulayat Land Registry (DaftarTanah Ulayat). Based on this registration, indigenous people may manage their customary land. They can further affirm their rights by applying for Land Management Rights (Hak Pengelolaan) or Freehold Title (Hak Milik) in the name of the indigenous people to ensure legal certainty. This study concludes that agrarian law reform provides indigenous people with recognition and protection to manage ulayat land.